Necrotizing enterocolitis (NEC): what's going on - Mario De Curtis; Gianluca Terrin (Hygeia Press di Corridori Marinella, 2013)
Necrotizing enterocolitis (NEC) is among the most common and devastating diseases in neonates and, despite the significant advances in neonatal care and clinical and basic science investigations, its etiology remains incompletely understood, specific treatment strategies are lacking, and morbidity and mortality from this disease remain high. Recent improvements in the pathophysiology of NEC may have therapeutic consequences. Toll-like receptors and intestinal microflora play an increasing role in the pathogenesis of NEC. Pharmacologic inhibition of TLR signaling, the use of novel nutritional strategies, and microflora modulation may represent novel promising approaches to the prevention and treatment of NEC. This review focuses on current and future therapeutic perspectives, starting from the recent acquisitions in the pathogenic mechanisms of NEC.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research